Effect of packaging materials and storage temperature on the shelf stability of Awaze paste - Kefale, Biadge; Delele, Mulugeta Admasu; Fanta, Solomon Workneh; Abate, Solomon (Frontiers in Nutrition, 2025)
BackgroundIt is well known that deterioration is a big concern in the food supply chain. The problem is more serious in handling of traditional foods in developing country such as Ethiopia, due to the limited knowledge about the optimum processing, packaging and storage conditions.ObjectiveThis study aimed to investigate the effect of packaging material and storage condition on the shelf life of Ethiopian traditional Awaze paste.MethodsSix types of packaging materials were employed: Shekella pot, Gourd (Qelle), high-density polyethylene (plastic bag), plastic bottle, glass bottle and metal can. These packaging materials are traditionally used by household producers and cottage industries in Ethiopia. The paste was stored at two temperatures: room temperature (21 ± 2°C) and refrigeration temperature (4°C).ResultsPhysical changes, color (a) value, pH, acidity, yeast and mold levels, total bacterial count (TBC), and lactic acid bacteria count (LAB) were assessed every 60 days over a period of 300 days. pH value, acidity, yeast and mold, TBC, and LAB count were significantly (p < 0.05) affected by packaging material, storage temperature and storage period. After 300 days of storage, the highest yeast and mold count, 4.06 log CFU/g, was observed in samples stored in plastic bags. The highest total bacterial count (TBC), 4.12 log CFU/g, was found in samples stored in metal cans. The samples stored in glass bottles at refrigeration temperature (4°C) were found to have a color (a*) value difference of 11.5 to 13.85, a yeast and mold count value of 3.2 log cfu/g, and a TBC value of 2.97 log cfu/g, which were acceptable after 300 days of storage as per the international food standards.ConclusionTaking into account all parameters including physical changes (color, mold growth, texture), acidity, yeast and mold, TBC, and LAB count, Awaze paste could be stored in glass bottles at 4°C for up to 300 days.